Students’ Knowledge Regarding Passive Smoking: A Cross-Sectional Study: Pengetahuan Mahasiswa Mengenai Perokok Pasif: Sebuah Studi Cross-Sectional - Hussein, Wathiq Faraon; Rahi, Eman H; Taqi, Riyadh Hussain (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Worldwide, smoking is a serious public health issue. While thousands of researchers have examined the health impacts of active smoking, less is known about the effects of passive smoking. Objectives: To identify the students’ knowledge regarding passive smoking. Methods: Nursing college students were given an electronic form to complete as part of a cross-sectional study aimed at evaluating their understanding of passive smoking. Convenient electronic sampling was employed. The study included a sample size of 150 University of Basra College of Nursing students at all levels. Results: We estimated that the population was composed of 61.4% Basra residents, 13.3% Thiqar residents, 10% Babylonians, 7.4% Baghdad residents, 6.6% Samawa residents, and 1.3% Dyala residents. 4% were older than 28, 80% were between the ages of 23 and 27, and 16% were between the ages of 18 and 22. They were divided into four stages: 22% in the first, 16% in the second, 18% in the third, and 44% in the fourth. The midnight study accounted for 30% of the sample, whereas the morning study accounted for 70%. Conclusion: Nursing college students are highly knowledgeable about the negative effects of passive smoking, as evidenced by the fact that the majority of the questionnaire's items were significant. Highlights: Smoking is a public health issue; passive smoking effects are under-researched. Assess nursing students' knowledge of passive smoking. Nursing students are knowledgeable about passive smoking's negative effects. Keywords: Students, Knowledge, Passive Smoking